Penyelesaian Sengketa di Segmen Noel Besi – Citrana antara Indoneia dan Timor Leste - Dewa Gede Sudika Mangku (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2019)
In Kupang District there is an unresolved segment, namely Noel Besi- Citrana, which is a disputed land along a river or delta starting from Co. 1745-6475 to Co. 1870-6770. The dispute area is located in Kupang Regency, with an area of ± 1,069 Ha, originating from the land dispute. When East Timor was still joining NKRI, the Noel Besi-Citrana area was the border area of Kupang Regency (NTT) and Ambeno Regency (Timor Leste region). The area of dispute is Naktuka which is located between the  Noel  Besi  River  and  the  Nono  Noemna  River.  Based  on  the Provisional Agreement in 2005 Article 6 point (b) which implies that local communities in this case the customary community / customary leaders  are  given  space  to  be  involved  in  the  process  of  resolving disputes that occur at the borders of the two countries by promoting peaceful and nonviolent means in accordance with Article 8 Provisional Agreement in 2005. Whereas the people who inhabit West Timor (Indonesia) and the people who inhabit East Timor (Timor Leste) have the   same   socio-cultural   background,  it   can   be   ensured  that   the customary law arrangements in force in these two community groups also  the  same. However, this  actually becomes an obstacle  when  the state takes the primary role, regardless of the Customary Figures who have the potential to determine the peaceful settlement of national borders in a family atmosphere..